AGENT AND STRUCTURE RELATIONS IN THE COMMUNICATION PROCESS BASED ON HUMANIST AND RELIGIOUS VALUES AT THE PAMULANG UNIVERSITY IN SOUTH TANGERANG - Surti Wardani; Alo Liliweri; Ridzki Rinanto Sigit (Bajang Institute, 2024)
Pamulang University (Unpam), one of the private universities in the South Tangerang area, is established to meet the needs of the community by providing its own uniqueness and receiving very good interest. The uniqueness meant by that is the history of its founding to provide higher education for all people, especially for those people mentioned, the increase and large quantity of registered students, the availability of classes for students with disabilities, adequate lecture facilities, affordable tuition fees, and no building costs. One of the successes that has been achieved to date is the contribution of lecturers in implementing the tridharma of higher education. This is where the lecturer acts as an agent, actor, or agency, as known in Anthony Giddens' structuration theory. As a form of routine that produces social practice, the lecturer's tridharma must reflect humanist and religious values, including in the communication process within the university. These two values are in accordance with those stated in the university's vision, namely,